When Does the Leader’s Positive Expression Get a Positive Response From Members? The Three-Way Interaction Effects of Perceived Deep/Surface Acting, Positive Affect, and Quality of Leader-Member Exchange on Work Engagement - Hong, Sung Hyoun; Kim, Min Soo (Frontiers in Psychology, 2021)
Although researchers have argued that a leader’s positive affective display effectively induces work motivation among members, it has not always resulted in desirable outcomes. This research addresses these critical issues and explains why individuals react differently, by considering the three-way interaction of the characteristics of expression, the positive affect of the members, and quality of LMX (Leader-member exchange). To verify our hypotheses, 698 days from 47 leaders and 146 members were collected through the Experience Sampling Method. The analysis was conducted using HLM, and the results showed that, for members with high quality LMX, the positive effect of perceived deep acting on work engagement was strengthened when positive affect was high, and the negative effect of perceived surface acting was weakened when positive affect was high. On the other hand, members with low-quality LMX showed a stronger positive effect of perceived deep acting on work engagement when positive affect was high, and the negative effect of perceived deep acting was mitigated when positive affect was low. These results demonstrate that quality of LMX serves as a context of the affective display between leaders and members, and the effect of displaying positive affect relies on members’ perception of the characteristics of the expression and the affective state.